2016
DOI: 10.1002/bio.3225
|View full text |Cite
|
Sign up to set email alerts
|

DPPH·–luminol chemiluminescence system and its application in the determination of scutellarin in pharmaceutical injections and rat plasma with flow injection analysis

Abstract: In this article, a DPPH·-luminol chemiluminescence (CL) system was reported and the CL mechanism was discussed according to the CL kinetic properties after sequence injecting DPPH· into the DPPH·-luminol reaction mixture. It was observed that scutellarin could inhibit the CL response of the DPPH·-luminol system. Based on this observation, a simple and rapid flow injection CL method was developed for the determination of scutellarin using the inhibition effect in alkaline medium. The optimized chemical conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Specht found that the older the stain, the brighter the reaction and the light-producing reaction. Because blood only known as a catalyst, the small hidden effects of the eye are sufficient to stimulate interaction, so use luminol to show blood spray and even ponds after removing [5][6][7]. Reaction lasts for a short time relative, resulting in half-minute glow, requiring low light conditions to capture, but strong enough to be recorded using images with a good camera.…”
Section: Luminolmentioning
confidence: 99%
“…Specht found that the older the stain, the brighter the reaction and the light-producing reaction. Because blood only known as a catalyst, the small hidden effects of the eye are sufficient to stimulate interaction, so use luminol to show blood spray and even ponds after removing [5][6][7]. Reaction lasts for a short time relative, resulting in half-minute glow, requiring low light conditions to capture, but strong enough to be recorded using images with a good camera.…”
Section: Luminolmentioning
confidence: 99%
“…Among these, the CL related to luminol (3‐aminophthalhydrazide) has been one of the most widely studied CL systems. Based on its efficient CL, luminol CL detection has been used in many fields for detection of various metal ions, reactive oxygen species, oxidants, etc . Inspired by the CL of luminol, some luminol analogues have been synthesized to achieve more efficient CL processes and expand the range of emission wavelengths (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested a critical role of oxidative stress in the development of lung injury induced by hind limb I-R (Kao et al, 2011). Scutellarin (4 0 ,5,6-trihydroxyflavone-7-glucuronide) is a flavonoid glycoside, which is the major antioxidant constituent extracted from the Chinese herb Erigeron breviscapus (Yao et al, 2017). Previous studies have reported its effectiveness in dilating blood vessels, improving hemodynamics and microcirculation, inhibiting platelet aggregation and increasing blood flow.…”
mentioning
confidence: 99%